2016
DOI: 10.1159/000443630
|View full text |Cite
|
Sign up to set email alerts
|

N-Carbamylglutamate Is an Effective Treatment for Acute Neonatal Hyperammonaemia in a Patient with Methylmalonic Aciduria

Abstract: N-carbamylglutamate (NCG) has been used in combination with ammonia scavengers (sodium benzoate, sodium phenylbutyrate) and dialysis to treat hyperammonaemia in methylmalonic aciduria (MMA). The sole use of NCG for acute neonatal hyperammonaemia secondary to MMA is demonstrated in a neonate presenting at day 9 with encephalopathy, severe metabolic acidosis, hyperammonaemia (1,089 μmol/l), ketonuria and urinary methylmalonic acids. Emergency treatment included discontinuing protein feeds, providing high calorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…There are reports on the rapid amelioration of patients’ clinical condition with precocious administration of NCG, regardless of the extent of hyperammonemia [ 7 11 ], suggesting that continuous NCG treatment may be effective. We report our highly positive clinical experience with continuous administration of NCG for 6 years in a patient with PA who presented frequently with hyperammonemia believed to reflect secondary blockage of NAG synthase by PA metabolites [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports on the rapid amelioration of patients’ clinical condition with precocious administration of NCG, regardless of the extent of hyperammonemia [ 7 11 ], suggesting that continuous NCG treatment may be effective. We report our highly positive clinical experience with continuous administration of NCG for 6 years in a patient with PA who presented frequently with hyperammonemia believed to reflect secondary blockage of NAG synthase by PA metabolites [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the use of nutritional approaches to optimize meat fatty acid composition has been a popular research topic, for example, supplying specific additives in diets such as linseeds, plant extracts [4,5]. The application of N-carbamylglutamate (NCG) as a dietary supplement for the health of humans and animals also has gained increasing interest [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of NCG in these cases was quite remarkable and significant reduction of ammonia levels was achieved within 12 h in most cases with a dose of 100–250 mg/kg/day. The observed responses obviated the use of scavenger medications or hemodialysis after the stabilization of ammonia levels [43,47,49,53]. Recent biochemical studies using heavy-isotope labeled urea precursors revealed that the administration of NCG accelerated the production of urea, validating the effectiveness of NGC in PA [8,9,54].…”
Section: Further Characterization Of Efficacy Of Ncg In Various Comentioning
confidence: 99%